Notes on the Iran Caddisflies and Role of Annulipalpian Hydropsychid Caddisflies as a Bio-monitoring Agent. - Naseh Malekei-Ravasan; Abbas Bahrami; Mansoreh Shayeghi; Mohamad Ali Oshaghi; Masomeh Malek; AllahBedasht Mansoorian; Hassan Vatandoost (Tehran University of Medical Sciences, 2013)
Background:  Eco-faunistic  studies  are  inevitable  step  in  environmental  researches.  Aquatic  organisms  like caddisflies are known as biological indicators for water quality assessment and water resource management. They have special role for energy flow in the freshwater habitats as food web and food chain among aquatic creatures. Methods: In addition to an extensive literature review on Iran Caddisflies, a field study was carried out in Lavasan river flows in north east of Tehran to collect aquatic insects using D-frame nets and or direct search on stone beneath. The water quality was measured using analytical method. Results: Literature revealed record of 62 trichopterid species in the country comprising 14 families. The most abun- dant species belonged to the Hydropsychidae. Herein we report presence of the Annulipalpian Hydropsyche sciligra H Malicky, 1977 in the study area. Habitat water quality of H. sciligra resembled human drinkable water. However presence of snail, Physa acuta and fish Capoeta buhsei in the water sampling area indicated inferior quality. Conclusion: From ecological point of view caddisfly larvae are predators of most important medical vectors like mosquitoes, blackflies and midges. Also they are useful and important indicator for monitoring physicochemical effects in the nature, so that they can be used for bio-monitoring program. From medical point of view, wing hairs or other body parts of caddisflies can be inhalant and contact allergens in Trichopterists and in sensitive individuals who come in contact.